Implementing Hyperlink PowerPoint Media for Teaching English as a Foreign Language at Junior High School - Prayoga, Kadek Agus; Padmadewi, Ni Nyoman; Pratiwi, Ni Putu Astiti (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
This study aims to analyze whether the use of digital media namely Hyperlink PowerPoint is affected or does not affect students' learning achievement. This research used mix method design which combines both quantitative and qualitative data collection. The population in this study was Junior High School with 2 samples, namely class VIIA and VIID. This study used a post-test-only control group design type. The scenario applied in this paper is described as one class (experiment group) was taught using digital media Hyperlink PowerPoint. On the other hand, the other class (control group) is taught using the conventional method. After several meetings, both classes were given a post-test. The post-test results were analyzed using SPSS 23 for t-test and size effect analysis to show if there was a significant difference between the two samples. The findings in this study are (1) The results of the T-test show that if the effect of the treatment using Hyperlink PowerPoint media gives significant achievement results to experimental students, the large difference measured using Cohen's size effect shows the number 0.051 or moderate category. (2) Results from the questionnaire showed positive results, namely: first, all students in the experimental group agreed with the use of Hyperlink PowerPoint media. Second, although there are 2 obstacles to the implementation, the activities can be carried out well. Third, after seeing the results found significant differences, the use of Hyperlink PowerPoint media deserves to be continually used as learning media.